High crimes [videorecording (DVD)] - Franklin, Carl, 1949-; Judd, Ashley; Freeman, Morgan; Caviezel, Jim, 1968-; Revell, Graeme (Twentieth Century Fox Home Entertainment, 2002)
High-profile attorney Claire Kubik puts her career on the line to defend her husband Tom Kubik after it is revealed that he is a Marine named Ron Chapman wanted for the murder of Latin American villagers.